2005
DOI: 10.1016/j.icesjms.2005.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Using size-based indicators to evaluate the ecosystem effects of fishing

Abstract: The usefulness and relevance of size-based indicators (SBIs) to an ecosystem approach to fisheries (EAF) are assessed through a review of empirical and modelling studies. SBIs are tabulated along with their definitions, data requirements, potential biases, availability of time-series, and expected directions of change in response to fishing pressure. They include mean length in a population, mean length in a community, mean maximum length in a community, and the slope and intercept of size spectra. Most SBIs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
329
1
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(353 citation statements)
references
References 91 publications
9
329
1
14
Order By: Relevance
“…In fact, t-tests reveal that the modern mean is not significantly different from that of five of the precontact assemblages (P < :01). This latter point is not an unexpected correlation; we know from modern management records that Gulf of Alaska cod populations are not overexploited (e.g., Thompson et al 2006Thompson et al , 2007 and therefore should not exhibit a significant harvesting-mediated size reduction (for a discussion of the relationship between average size and exploitation pressure see Shin et al [2005]). We have previously suggested ) that modern fisheries practices are largely maintaining the preindustrial population structure of Pacific cod, and, therefore, using sized-based indicators as a metric, modern cod harvest practices appear to be ''sustainable.''…”
Section: Faunal Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…In fact, t-tests reveal that the modern mean is not significantly different from that of five of the precontact assemblages (P < :01). This latter point is not an unexpected correlation; we know from modern management records that Gulf of Alaska cod populations are not overexploited (e.g., Thompson et al 2006Thompson et al , 2007 and therefore should not exhibit a significant harvesting-mediated size reduction (for a discussion of the relationship between average size and exploitation pressure see Shin et al [2005]). We have previously suggested ) that modern fisheries practices are largely maintaining the preindustrial population structure of Pacific cod, and, therefore, using sized-based indicators as a metric, modern cod harvest practices appear to be ''sustainable.''…”
Section: Faunal Studiesmentioning
confidence: 86%
“…The ability to do such analysis is critical because fish grow throughout their life span, and thus most life history traits in fish stocks are correlated with size (Reiss 1989). Size is therefore an important metric in modern fisheries management research (e.g., Shin et al 2005). As a result, allometric analysis can provide a crucial means to compare the preindustrial fisheries record with modern fisheries management data.…”
Section: Faunal Studiesmentioning
confidence: 99%
“…Many size-based indicators (SBIs) have been proposed to quantify the effects of fishing on marine foodwebs, and they have been compared in several studies (e.g. Shin et al, 2005). Blanchard et al (2010) showed how time-series of community-level indicators, including SBIs, reveal strong effects of selective fishing, but no study has so far measured the relative importance of individual-level effects compared with species-level effects.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined weight frequencies of striped marlin but the duration of the 79-year (7 years missing) time series examined in this study is unprecedented (Kume & Joseph 1969;Merrett 1971;Pillai & Ueyanagi 1978;Squire 1983). A reduction in individual size is common among commercially exploited fish species but a significant shift in size structure may indicate overexploitation (Shin et al 2005). Similar but more rapid trends of decreasing mean size have occurred in a variety of other pelagic teleost and oceanic shark species (Baum et al 2003) but the decrease becomes particularly concerning when mean size drops below size at maturity (Baum & Myers 2004).…”
Section: Discussionmentioning
confidence: 98%